Numerical Analysis of the Effect of Microscale Components Interaction on Measurements of Fiber Optic Strain Sensors Used in Composite Structures - Mikhail Tashkinov; Igor Shardakov (Advances in Materials Science and Engineering)
The paper investigates the influence of structural components of a composite material on the strain values measured by using an embedded optical fiber with Bragg gratings. The effect of composite plies and intermediate epoxy layers on the transfer of deformations from the measured object to the optical fiber was studied taking into account various methods of the fiber attachment and surrounding media configurations. A numerical estimation of the effect of the longitudinal and transverse components of the strain tensor on the wavelength of the reflected spectrum is performed.